Virtual Field Trip dan Penggunaannya sebagai Fasilitator dalam Mengembangkan Keterampilan Komunikasi Abad ke-21 Siswa - Amala, Hanifa Ahsanu; Amprasto, Amprasto; Solihat, Rini (Department of Biology Education, Universitas Pendidikan Indonesia, 2019)
This study using virtual field trip as a facilitator to developing 21st century skill in student. The use of virtual field trip is for developing an innovation of field trip which is visualized as internet based to provide trips on the field without leaving the classroom. This study aimed to facilitate the development of one of 4Cs component, which is communication of the 21st century skills using virtual field in ecosystem. There are 30 students (N=30) of 10th grade in science class at senior high school 20 Bandung became subject. The instrument using eight question for assessed written communication skill, observation rubric for assessed verbal communication skill, and response questionnaire. Through the result, we found thatstudent’s written communication skill has been increasing and included as a middle category of N-gain. The observation showed that students having a good profile on verbal communication skills. This result has been supported by the questionnaire which is all students say agree (57%) and very agree (43%) with the statement that this method help to make learning ecosystem became more interesting and perceivable.